Organic Photovoltaics on Greenhouse Rooftops: Effects on Plant Growth. (2019) - Zisis, C.; Pechlivani, E.M.; Tsimikli, S.; Mekeridis, E.; Laskarakis, A.; Logothetidis, S.
Abstract: Greenhouse agriculture is a high-growth and high-volume market that rapidly expands worldwide to address the societal needs for food production. The increasing demand for energy to cover their requirements, coupled with the limited amount of available fossil fuels, has turned the agriculture community in the exploitation of renewable energy sources. Intensive research is currently focuses on the use of solar energy in agriculture constructions. Organic Photovoltaics (OPVs) are constantly gaining ground among other PV technologies due to their low weight, tunable optical transmittance, flexibility and high conformability. In this work, semi-transparent OPVs based on the blend of regioregular poly(3-hexylthiophene) (P3HT) and phenyl-C61-butyric acid methyl ester (PCBM) were integrated on the rooftop of the 24 m 2 experimental Mediterranean greenhouse covering the 22% of its total area in order to investigate its effect on the growth and behavior of cultivated pepper plants ( Capsicum annuum ). Under the shade of OPVs, the pepper plants produced 20.2% more fruit mass compared to the control ones. In addition, at the end of the growing season, the height of the shaded plants was 21.8% larger than the remaining plants.